Enhancing EFL students’ speaking ability through project-based learning: A study at an Indonesian university - Oktavia, Diana; Habibah, Nur; Lestari, Renda; Kurniawan, Ridho (Universitas Jambi, Indonesia, 2026)
This study examines the effectiveness of Project-Based Learning (PBL) in improving English as a Foreign Language (EFL) students’ speaking ability at Universitas Muhammadiyah Muara Bungo. A mixed-method design was employed, involving second-semester students of the English Education Department. Data were collected through speaking performance assessments and open-ended surveys. Quantitative results indicated a significant improvement in students’ speaking scores, with the average increasing from 78 to 88 across project tasks. Qualitative findings revealed enhancements in vocabulary, grammar, fluency, and confidence. Students reported that repeated practice, collaborative work, and authentic speaking tasks contributed to reduced anxiety and improved performance. The findings suggest that PBL not only enhances linguistic competence but also supports psychological readiness in speaking. Therefore, integrating project-based activities into speaking instruction is recommended to promote active learning and improve students’ communicative competence.